Deciphering the role of BMP4 signalling and gene regulation in the specification of human liver progenitor cells - Durczak, Paulina Maria (2023)
Early hepatic specification and organogenesis can be modelled in vitro using human induced pluripotent stem cells (hiPSCs). These models apply differentiation protocols to direct hiPSCs through all the key developmental stages to accurately reflect in vivo development. Bone morphogenetic protein (BMP) and fibroblast growth factor (FGF) signalling are crucial for the specification of hepatic progenitors during early liver development. While the signalling cascades of these two morphogens are well characterized, the mechanisms by which they promote hepatic cell fate choice and hepatic gene expression in anterior foregut endoderm (FE) cells is not very well understood.